Cage-like microstructures via sequential Ugi reactions in aqueous emulsions - Alqubelat, Rita S.; Menzorova, Yaroslava A.; Mironov, Maxim A. (Beilstein Journal of Organic Chemistry, 2024)
Cage-like microstructures were obtained in two steps by sequential Ugi reactions. At the first stage, submicron colloidal particles based on carboxymethylcellulose and chitosan with a domain structure were obtained in an aqueous suspension. In the second stage, the Ugi reaction was carried out on the surface of the Pickering emulsions with toluene. Removal of toluene and redissolution in water resulted in colloidosomes with large holes on the surface. Varying the cross-link density during the Ugi reaction made it possible to obtain structures with different hole sizes.
Keywords: carboxymethylcellulose; chitosan; colloidosomes; Pickering emulsions; Ugi reaction